Penerapan Multimedia Animasi untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar (Studi Eksperimen di Kelas IV SD Negeri 18 Pekanbaru) - Rufaidah, Ummi; Alpusari, Mahmud; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThis study is done due to a low stundents’ science study results in learning process. The purpose of this study is to compare the study results between the class with animation multimedia learning media and the class with image media. The method used in this study is the quasi experimental with pretest-posttest control group design. The subjects of this study are the students from SD Negeri 18 Pekanbaru year 2012/2013. Two samples for this study are class IV A with total 32 students and class IV B with total 32 students which chosen by random assignment. The data collected for this study are from students’ study results in science by a test, to complete this data we used students’ behavior on science questionnaires. Based on that data analysis results, we conclude that: 1) There is an increase in study results on both observed class. The increase can be seen from the average of initial test results of experiment class that is 60,37 and became 76,62 at the final test with average gain index reached 0,41 with medium category, while the average of initial test results of controlled class is 61,25 and increased to 62,62 on the final test with average gain index reached 0,05 which belong to low category. One can conclude that there is an increase in students’ study results on science of the students in class IV SD Negeri 18 Pekanbaru. 2) The students’ study results on science which used animation multimedia learning have a significant enhancement difference than that of the students with image media learning. This difference is known by average gain index difference test between the experiment class and the controlled class using t-test and obtained that tcount is 3,39 while ttable is 1,67.Keywords: Study results and animation multimedia.